2019
DOI: 10.3389/fcell.2019.00070
|View full text |Cite
|
Sign up to set email alerts
|

Akt-ing Up Just About Everywhere: Compartment-Specific Akt Activation and Function in Receptor Tyrosine Kinase Signaling

Abstract: The serine/threonine kinase Akt is a master regulator of many diverse cellular functions, including survival, growth, metabolism, migration, and differentiation. Receptor tyrosine kinases are critical regulators of Akt, as a result of activation of phosphatidylinositol-3-kinase (PI3K) signaling leading to Akt activation upon receptor stimulation. The signaling axis formed by receptor tyrosine kinases, PI3K and Akt, as well as the vast range of downstream substrates is thus central to control of cell physiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 323 publications
3
105
0
Order By: Relevance
“…In agreement with the effect observed after TMEM167A downregulation in gliomas cells, it has been shown that RAB7 is essential for AKT activation and signaling in other cancer cells [30]. Moreover, there is plenty of evidences supporting the existence of a tight regulation of the spatial and temporal compartmentalization of AKT activation and function [9].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In agreement with the effect observed after TMEM167A downregulation in gliomas cells, it has been shown that RAB7 is essential for AKT activation and signaling in other cancer cells [30]. Moreover, there is plenty of evidences supporting the existence of a tight regulation of the spatial and temporal compartmentalization of AKT activation and function [9].…”
Section: Discussionsupporting
confidence: 67%
“…Additional mechanisms contribute to increase EGFR signaling, like interaction with other receptors and amplification or overexpression of extracellular ligands [1,2]. Moreover, several endocytic/recycling molecules contribute to the stabilization of EGFR in gliomas and other cancers, increasing the robustness of the signaling cascade and/or relocating the activation of the downstream targets [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Dasatinib was first characterized as a potent Src/Abl inhibitor, and subsequently has also been shown to target receptor tyrosine kinases (RTKs) including PDGFR, KIT and EPH receptor family members EPHA2 and EPHB1 23 . PI3K-Akt signaling is activated by RTKs, such as PDGFR and KIT, as well as non-receptor Src family kinases (SFKs) 41,42 , and therefore by inhibiting these upstream kinases, dasatinib treatment can lead to attenuation of activated Akt. Our study confirmed expression of AZD2014 and dasatinib targets in all human VS tumors tested, and we therefore chose to further evaluate dasatinib because it has the advantage of simultaneously inhibiting multiple signaling pathways observed in NF2-associated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The serine/threonine kinase AKT is a master regulator of many diverse cellular functions, including survival, growth, metabolism, migration, and differentiation. The signaling axis formed by PI3K and AKT, as well as the vast range of downstream substrates is thus central to control of cell physiology in many different contexts and tissues (Noorolyai et al, 2019;Sugiyama et al, 2019). Matrine inhibits the PI3K/ AKT pathway in tumor cells, while the reverse occurs in normal cells (Niu et al, 2014;Xie et al, 2015;Liu S. Q. et al, 2017;Wu X. et al, 2017;Chen et al, 2019;Zhang et al, 2019).…”
Section: Discussion and Prospectmentioning
confidence: 99%